Resonant microwave pulse compression at an output of the relativistic magnetron; Doklady Akademii Nauk; Vol. 366, № 5 - Didenko A. N. Andrei Nikolaevich; Vintizenko I. I.; Mashchenko A. I.; Ryabchikov A. I. Aleksandr Ilyich; Fomenko G. P.; Chumerin P. Yu. Pavel Yurievich; Yushkov Y. G. Yuri Georgievich (1999, 1999)
В фонде НТБ ТПУ отсутствует